2016
DOI: 10.1136/bcr-2016-216201
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of treating incidental synchronous bilateral breast cancer with differing tumour biology

Abstract: A 59-year-old woman with right breast mass was diagnosed with invasive ductal carcinoma (IDC). Workup consisted of bilateral diagnostic mammogram and ultrasound (US); both showed a right breast mass with normal left breast. Core biopsy showed IDC with estrogen receptor negative (ER-)/progesterone receptor negative (PR-) and HER2/neu positive receptor status. The patient underwent carboplatin-based chemotherapy with Herceptin. The mass completely resolved. The patient desired to proceed with bilateral total mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The initial search registered a total of 95 records, of which 20 were excluded for duplication, 28 for not corresponding to molecular subtype discordance, 20 for lacking case presentations, 8 for not corresponding to breast cancer, and 6 for corresponding to basic science topics. Only four previously published reports of SBBC with molecular subtype discordance were found ( Table 1), illustrating the limited literature available for this entity [4,9,[11][12]. The age at diagnosis in these reports was between 48 and 60 years, making our patient the youngest reported case to date.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The initial search registered a total of 95 records, of which 20 were excluded for duplication, 28 for not corresponding to molecular subtype discordance, 20 for lacking case presentations, 8 for not corresponding to breast cancer, and 6 for corresponding to basic science topics. Only four previously published reports of SBBC with molecular subtype discordance were found ( Table 1), illustrating the limited literature available for this entity [4,9,[11][12]. The age at diagnosis in these reports was between 48 and 60 years, making our patient the youngest reported case to date.…”
Section: Discussionmentioning
confidence: 81%
“…The age at diagnosis in these reports was between 48 and 60 years, making our patient the youngest reported case to date. Discordance in hormone receptor status occurred in all cases, while discordance in HER2+ status occurred in only two cases [4,12]. All cases received neoadjuvant chemotherapy, which was followed by bilateral modified radical mastectomy (MRM) in three patients [4,[11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esclovon et al [10] reported a 59 years old woman with ER and PR negativity and HER2 /neu positivity on the right breast mass and the opposite results on the incidentally found left breast invasive ductal carcinoma. This different biological behavior mandates different treatment modalities for each side.…”
Section: Discussionmentioning
confidence: 99%